ANALISIS HUBUNGAN JENIS KEMOTERAPI DENGAN PERBAIKAN OUTCOME DAN BIAYA PENGOBATAN PADA PASIEN KANKER PAYUDARA DI RSUD DR. MOEWARDI - , Septianita Hastuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The process of chemotherapy often brings unpleasant side-effects to patients. Moreover, types of chemotherapy give impacts to the total cost treatment for patients. This research aims to give illustration of chemotherapy regimens to its outcomes (monitored by the interval between chemotherapy and radiotherapy) and medical costs illustration for the breast cancer patients at RSUD Dr. Moewardi. This is a descriptive research with hospital perspective. Data collecting method used was retrospectively. Those data were taken from medical records and medical payment records of the patients. The subject of this research is breast cancer inpatients who passed the inclusion criteria during the period of January 2010 â January 2012 at RSUD Dr. Moewardi. Number of population are 106 patients. Data analysis was completed using chi â square with cross tab and One Way Anova test. Test result showed that breast cancer patients who took CAF chemotherapy was 43,40%, CA was 32,10%, CisT was 17,90% and AT was 6,60%. CisT chemotherapy had worse outcomes illustration than the others chemotherapy, yet it did not have any significant improvement of the outcomes. Medical cost for breast cancer patients with CisT chemotherapy was Rp. 16.767.014,20. It was much higher than AT chemotherapy (Rp. 8.305.309,01) CAF chemotherapy (Rp. 6.550.651,46) and CA chemotherapy (Rp. 5.824.591,89). The proportion of medical costs for AT chemotherapy spent the most on chemotherapy medicine cost, while for CAF, CisT, and CA spent the most on its surgical act costs.